DEFICIENT INHIBITION AS AN EXPLANATORY HYPOTHESIS OF MEMORY CHANGES IN THE ELDERLY - Pousada Fernández, Modesta (Anales de Psicología / Annals of Psychology, 1998)
One of the hypothesis proposed in order to explain age associated memory impairment accounts for the changes in memory processes in the elderly calling on inefficient inhibitory mechanisms. Accordingly with this point of view, efficiency in cognitive inhibition would decline with age, so that the elderly would be less able to maintain out of working memory irrelevant information or, as the goal of the task changes, to ignore no longer relevant thoughts or actions. The aim of our paper is to review the theoretical background and the main experimental results of this hypothesis from when it was proposed by Hasher and Zacks in 1988 up till now.